Mechanisms behind the death feigning behaviour in Tetramorium quadrispinosum in the Cape Floristic Region, Western Cape, South Africa - Peters, Bryone Marshalene (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.